From toad to frog: osteological description and taxonomic reattribution of the 'mummified' holotype of Bufo servatus, an Eocene anuran, based on micro-CT examination - (:unkn) unknown (My University, 2021)
The Quercy Phosphorites are a set of Eocene-Oligocene deposits from South-West France that yielded numerous vertebrate fossils, including amphibians, mostly as isolated bones. However, in 1873, several exceptional amphibian specimens were discovered, with the external surface of the unmineralized tissues preserved, and were commonly referred as “mummies”. In the 19th century, they were described without any knowledge of their internal anatomy. Since 2012, we have started scanning these “mummies”, revealing the preserved internal soft tissues and articulated skeleton. A first specimen was attributed in 2013 to Thaumastosaurus gezei and we here present our results from the tomography of a second “mummified” anuran, previously identified as Bufo servatus. The tomography showed a preserved articulated skeleton, and its osteological characteristics are similar to the first scanned anuran “mummy”, representing different ontogenetic stages. Both are now both attributed to Thaumastosaurus servatus nov. comb. The new anatomical information is used to assess the affinities of T. servatus, which appears to belong to the Pyxicephalidae, an African anuran clade. Thaumastosaurus thus represents both the oldest occurrence of this clade in the fossil record and its first occurrence outside of Africa. Its presence in Europe highlights a faunistic exchange with Africa during the Eocene, also documented for several clade of squamates. The presence of this African herpetofauna in Europe might be linked to the warmer climate during the Eocene. However, most of this herpetofauna, including Thaumastosaurus, disappeared from the region around an extinction event (named the “Grande Coupure”) that took place around the Eocene/Oligocene transition (~34 Ma)
Keywords: African Research